2020
DOI: 10.1016/j.jss.2019.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Acute Cholecystitis: An Analysis of Cholecystectomies Spanning Three Decades

Abstract: Seasonal variation in acute cholecystitis: An analysis of Seasonal variation in acute cholecystitis: An analysis of cholecystectomies spanning three decades cholecystectomies spanning three decades

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In 2012, the US reported that 215,995 patients were diagnosed with acute cholecystitis, resulting in a direct cost of US $9.3 billion. 1 In the UK, acute cholecystitis accounts for approximately one‐third of all unplanned general surgical admissions. Historically, UK centers have reported a variable percentage of units able to perform laparoscopic cholecystectomy to these patients in the first 10 d of presentation, ranging from 0% –35%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, the US reported that 215,995 patients were diagnosed with acute cholecystitis, resulting in a direct cost of US $9.3 billion. 1 In the UK, acute cholecystitis accounts for approximately one‐third of all unplanned general surgical admissions. Historically, UK centers have reported a variable percentage of units able to perform laparoscopic cholecystectomy to these patients in the first 10 d of presentation, ranging from 0% –35%.…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of people develop symptoms of acute cholecystitis annually across the world, with a resulting high management cost. In 2012, the US reported that 215,995 patients were diagnosed with acute cholecystitis, resulting in a direct cost of US $9.3 billion 1 . In the UK, acute cholecystitis accounts for approximately one‐third of all unplanned general surgical admissions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, seasonal variations in intussusception suggest that infectious or climatic conditions contribute to its pathogenesis [4,[6][7][8]. Epidemiological similarities, such as seasonality, may provide clues to the links between surgical conditions and communicable diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cardiac arrest and asthma have been reported to be most common in winter [10,11]. Similarly, several studies have reported that the frequency of acute appendicitis was higher in summer [12,13], and some have reported that admissions for diverticulitis and acute cholecystitis were more common in summer [12,14,15]. However, seasonal variations in the severity of acute abdomen have been reported less frequently, especially in Japan.…”
Section: Introductionmentioning
confidence: 99%